ChemInform Abstract: Ca[LiAl3N4]:Eu2+ — A Narrow‐Band Red‐Emitting Nitridolithoaluminate. Issue 33 (19th August 2014) - Pust, Philipp; Wochnik, Angela S.; Baumann, Elen; Schmidt, Peter J.; Wiechert, Detlef; Scheu, Christina; Schnick, Wolfgang
Abstract Ca[LiAl3N4]:Eu2+ is prepared by firing a mixture of Ca, LiAlH4, LiN3, AlF3, and 5 mol% EuF3 (Ta ampules, 1000 °C, 4.5 h).